Spasialisasi dan Praktik Monopoli Emtek Group - Muhammad Dicka Ma'arief Alyatalatthaf (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
This study aims to determine the form of spatialization and monopolistic practices carried out by Emtek Group. This research uses descriptive qualitative in the critical analysis perspective of the Political Economy of Communication Theory by Vincent Mosco. The political economy of communication theory  is used to describe the spatialization in the form of horizontal integration and vertical integration to strengthen the organization and to dominate market. This research uses documentation data collection techniques by observing and analyzing the business units of the Emtek Group and the historical record establishment of Emtek Group including the shift of shareholders from Emtek Group and its subsidiaries. The result shows that the spatialization carried out by Emtek Group has caused monopoly, monopsony and conglomeration practices that can threaten the principle of fair business competition. In addition, the practice of conglomeration also provides an imbalance effect on television content, between programs containing entertainment with information programs. Seeing these conditions, society must participate in terms of surveillance by acting as a watchdog, so that media corporations can be controlled more objectively. The government should provide detail information about the proportion between information and entertainment in television program content, and should restrict media cross-ownership.